Role of environmental and occupational factors in fall‐related maxillofacial fractures - Nigam Sattar; Syeda Rabia Rahat Gillani; Mahwish Erkin; Muslim Khan; Maryam Abbas; Nimrah Khurshid khattak (Wiley, 2022)
Abstract Objectives The objective of this study was to determine the frequency and patterns of maxillofacial fractures in falls due to environmental and occupational reasons. Material and Methods One hundred and nineteen patients were included in this study who presented to the department of Oral and maxillofacial surgery at Khyber College of Dentistry, Peshawar. The duration of study was 3 years from January 1, 2017 to December 31, 2019. Demographic data such as age, gender and data environmental or occupational etiology of falls and pattern of fractures was noted in a customized Performa after detailed history, clinical and radiographic examination. Patients of maxillofacial fractures resulting due to falls with age ranging from 16 to 64 years were included. Those cases of falls that presented with systemic diseases or had chances of pathological fractures were excluded from the study. Results Male population was affected more than females (60% vs. 39.4%). The mean age was 32.39 SD ± 16.031. Falls due to environmental factors were more common than occupational factors (81.5% vs 18.5%). Fracture of midface was more common (57.1%) than fracture of mandible (36.7%) in patients of falls. 5.5% had both midface and mandible fractures. Conclusion We concluded that Environmental and work‐related facial fractures in falls are common in third and fourth decade of life. Falls due to stumbling, tripping and slipping, falls from height and falls from stairs most commonly result in midface fractures. Mandible fractures are commonly seen in sportsmen and laborers. Preventive strategies shall be adopted to prevent morbidity and mortality associated with such injuries.